Evaluation of Corynocarpus laevigatus extract as a green corrosion retardant for mild steel in acidic media: A combined gravimetric, gasometric and electrochemical methods - Anthony I. Obike; K.S. Eze; Ibrahim Abdel-Rahman; Alexander I. Ikeuba; Izuchukwu K. Nwokolo; Christopher Aghalibe (Current Research in Green and Sustainable Chemistry)
The corrosion inhibition by the methanolic extract of Corynocarpus laevigatus leaves on mild steel within acidic environments was evaluated utilizing gravimetric, gasometric, and electrochemical methodologies. The findings indicate that the extracts serve as an effective corrosion inhibitor in both H2SO4 and HCl aqueous solutions. The extract exhibited optimum inhibition efficiencies of 88.64 %, 71.12 %, and 77.60 % in H2SO4, and 88.89 %, 67.96 %, and 85.55 % in HCl, respectively. The inhibition efficiency increased with higher extract concentrations but decreased with increasing temperature and exposure time in both media. Also, the rate of hydrogen evolution increased with rising temperature in both media. Adsorption studies revealed that the inhibitor's average activation energy (Ea) values were 71.23 kJ/mol and 137.59 kJ/mol for H2SO4 and HCl media, respectively. The extract followed the Langmuir isotherm model, indicating monolayer adsorption of the phytochemical components onto the mild steel surface. Physical adsorption was dominant in H2SO4, as evidenced by decreasing activation energy (Ea) values with increasing temperature. In contrast, chemical adsorption was observed in HCl. The strong adsorption of phytochemicals present in the extract onto the steel surface was identified as the primary mechanism for corrosion inhibition. This study provides valuable insights into the dual adsorption mechanisms of Corynocarpus laevigatus in different acidic media which underscores its potential as a sustainable and effective corrosion inhibitor in acidic environments.